Blastomycosis in a Young African Man Presenting with a Pleural Effusion. Issue 8 (2006) - Alvarez, GG; Burns, BF; Desjardins, M; Salahudeen, SR; AlRashidi, F; Cameron, DW
Abstract : Blastomyces dermatitidis is a dimorphic fungus endemic to northwestern Ontario, Manitoba and some parts of the United States. The fungus is also endemic to parts of Africa. Pulmonary and extrapulmonary findings of a 24-year-old African man who presented with weight loss, dry cough and chronic pneumonia not resolving with antibiotic treatment are presented. The unusual occurrence of pulmonary blastomycosis associated with skin lesions and a moderate pleural effusion is reported.